تأثير الكادميوم والرصاص في نفوق اصبعيات الكارب العادي Cyprinus carpio المستزرعة في مزرعة السن (Latakia University Journal -Biological Sciences Series, 2019)
تمت دراسة تأثير خمسة تراكيز متدرجة من الكادميوم والرصاص (على شكل كبريتات الكادميوم المائية ونترات الرصاص على التوالي) على زمن نفوق اصبعيات الكارب العادي carpio Cyprinus بمتوسط وزن (0.49±0.08غ و29.31±1.71غ) المستزرعة في مزرعة السن )بانياس). تبين أنّ لكبريتات الكادميوم المائية تأثير أقوى على اصبعيات الكارب ذات الوزن (0.49±0.08غ) إذ كانت نسبة النفوق مرتفعة في اليوم الرابع من التجربة عند التركيز( 2.5 ملغ/ل)، بينما كان لنترات الرصاص تأثير أقل على النفوق إذ لم تنفق أي فرد سمكي خلال الأيام الثلاثة الأولى، إنما ارتفعت نسبة النفوق عند التركيز (2.5 ملغ/ل) في اليوم السادس للتجربة. كما تبين عند التراكيز الأعلى من الكادميوم والرصاص المستخدمة على الاصبعيات  بوزن (29.31±1.71غ) أنّ لكبريتات الكادميوم المائية  تأثير أقوى من نترات الرصاص على نفوق الأسماك، إذ كانت نسبة النفوق مرتفعة في اليوم الخامس للتجربة عند التركيز(16 ملغ/ل) من كبريتات الكادميوم، بينما ارتفعت نسبة النفوق في التركيز (32 ملغ/ل) من نترات الرصاص في اليوم السابع من التجربة. تدل هذه النتائج أن للكادميوم تأثير سمي أعلى من الرصاص على نفوق الأسماك ذات الأوزان (0.49±0.08غ و29.31±1.71غ) وذلك بالنسبة للتراكيز المستخدمة وللفترة الزمنية ذاتها خلال التجربة. The aim of this study was to determine the effect of five gradient concentrations of cadmium and lead (cadmium sulfate and lead nitrate) on the mortality of common carp fingerlings (Cyprinus carpio), with average weight of 0.49±0.08g and 29.31±1.71g of the AL-sin farm. The results showed that hydrophilic cadmium sulphate had stronger effect on carp fingerling weighing (0.49±0.08g) where the mortality percentage was high by the fourth day of the experiment in the concentration (2.5 mg / L).  Lead nitrate had  lesser effect on mortality, no where individual has died during the first 3 days. The mortality rate increased in the concentrations (2.5 mg / L) by the sixth day of the experiment. The higher concentrations of cadmium and lead (29.31±1.71g), the cadmium hydroxide sulfate showed stronger effect than the lead nitrate on fish mortality. The mortality rate was high by the fifth day with the concentration (16 mg / L) of Cadmium sulphate, while with the concentration (32 mg / L) of lead nitrate, the mortality rate increased by the seventh day of the experiment. These results indicate that cadmium has stronger toxic effect than lead on the mortality of fish weighing (0.49±0.08g and 29.31±1.71g) with the concentrations and some time periods used during the experiment.